Pre-Eclampsia Placental Carbohydrate Metabolism Regulating Enzymes Activity - Oré, Raquel (1996)
Pre eclampsia is one of the most frecuent pathologies during pregnancy. The placental tissue plays an important role in the development of the pathology. In this report we performed a study of the activities of two regulatory enzymes [ Phosphofructokinase I (E.C. 2.7.1.11) and Glucose 6-P-dehidrogenase (E.C. 1.1.1.49)] of the carbohydrate metabolism in both normal and pre emclampsia placental tissue. It has been found a pronounced decreased in both activities in the pathological tissue. We discussed the possible mechanisms.